Effectiveness of simulation-based interprofessional education on teamwork and communication skills in neonatal resuscitation - Shinhye Chae; Soonyoung Shon (BMC Medical Education, 2024)
Abstract Background The role of effective interprofessional teamwork is especially vital in the Neonatal Intensive Care Unit (NICU) where infants facing emergency situations are admitted. Proper neonatal resuscitation, facilitated by comprehensive resuscitation training, can significantly decrease the mortality rates associated with neonatal asphyxia and respiratory failure. This study aimed to develop a simulation-based interprofessional education (IPE) programme for medical staff working in a nursery and NICU and to assess its effectiveness on teamwork, communication skills, clinical performance, clinical judgement, interprofessional attitudes, and education satisfaction. Methods Through a demand survey, neonatal resuscitation was selected as the theme, and an IPE team comprised of one doctor and two nurses was formed. The education programme consisted of three sessions lasting a total of 140 min: two simulation exercises and one theoretical education session. Data were collected from 18 nurses working in the nursery and NICU and 9 doctors working in the paediatrics department. Results A comparison of the metrics before and after applying simulation-based IPE programmes revealed teamwork (Z=-2.67, p = .008), communication skills (Z=-2.68, p = .007), clinical performance (Z=-2.52, p = .012), clinical judgement (Z=-4.52, p < .001), and interprofessional attitude (Z=-3.64, p < .001) to have significantly improved. Education satisfaction scores were 4.73 points on average out of a maximum of 5. The simulation-based IPE programme was effective in improving the teamwork, communication, and clinical performance of resuscitation teams, individual clinical judgement, and interprofessional attitude. Conclusions Simulation-based IPE is effective for enhancing teamwork, team communication, clinical judgement skills, and clinical performance in neonatal resuscitation. This programme has the potential to contribute to the improvement of patient safety and the quality of neonatal care. Additional studies are needed to longitudinally examine the effects of the programme on patient safety and quality of neonatal care.